National Alliance for Radiation Readiness: Leveraging Partnerships to Increase Preparedness. Issue 2 (February 2016) - Blumenstock, James S.; Allen, Meredith
Abstract: The National Alliance for Radiation Readiness (NARR) is an alliance of 16 national member organizations that have banded together to serve as the collective "voice of health" in radiological preparedness through: participation in national dialogues on radiological emergency issues; provision of thoughtful feedback on documents, policies, and guidelines; and convening of partners to raise awareness of and resolve radiological emergency issues. NARR benefits from the intersection and interaction of public health, radiation control, healthcare, and emergency management professionals—all with an interest in bolstering the nation's preparedness for a radiological or nuclear incident. NARR is able to provide a unique perspective on radiological and nuclear preparedness by creating multi-disciplinary workgroups to develop guidance, recommendations, and provide subject matter feedback. NARR aims to build response and recovery capacity and capabilities by supporting the sharing of resources and tools, including technical methods and information through the development of an online clearinghouse. NARR also aims to identify and disseminate best practices, as well as define and educate on the roles and responsibilities of local, state, and federal government and the numerous agencies involved with the response to a radiological emergency.